(untitled) (INNOVATIVE ECONOMY, 2024)
Lotysh O.Ya., Kostetska N.I. ADAPTATION OF BUSINESS MODELS FOR THE DEVELOPMENT OF UKRAINIAN AGRICULTURAL ENTERPRISES TO THE CURRENT ECONOMIC CHALLENGES Purpose. The aim of the article is to analyse the state of the agro-industrial complex and substantiate the directions for the adaptation of business models for the development of agrarian enterprises in Ukraine during the military challenges. Methodology of research. The theoretical and methodological basis of the research is the scientific works of leading scientists and businessmen-practitioners in the agricultural sector of Ukraine. In the research process, the following general scientific methods were used: comparison method – for the study of business models of the development of subjects of the agro-industrial complex; analysis and synthesis – to analyse the state of development of agro-industrial complex enterprises; abstract and logical method – for expressing one’s own assumptions and formulating conclusions, graphic method – for visual illustration of the dynamics of the development, losses and damages of the agricultural sector. Findings. It was concluded that the formation of an adaptive business model should take into account both the internal and external factors of the functioning of an agricultural enterprise in conditions of Russia’s military aggression in Ukraine. The indicators of the development of the field of crop production, as one of the structural factors in the country’s economy, as well as direct losses and indirect losses in crop production and livestock production caused by the war, were analysed. It was found that a feature of the agro-industrial complex of Ukraine is the presence of a significant share of agricultural holdings and farms and personal farms in it. It was emphasized on the fact that the war had caused additional negative aspects of the functioning of the agroholding model of the Ukrainian agricultural industry, in particular, the breakdown of logistics chains, environmental disasters at the livestock complexes of agroholdings, the blocking of sales markets showed the low adaptability and inability of such enterprises to respond in time to the challenges of wartime. Originality. The features of business models adaptation for the development of agrarian enterprises, taking into account both direct and indirect losses due to Russian aggression, have gained further development. The comparison of the modern models of the functioning of the agro-industrial complex in Ukraine made it possible to identify the disadvantages of the agricultural holding model and to propose the directions for state support for the development of the farming business model in conditions of modern challenges. Practical value. The results of the study can be used for the analysis and adaptation of business models of agricultural enterprises in the war and post-war period. Key words: agro-industrial complex, plant breeding, livestock breeding, business model, adaptation, farms, agricultural holdings.